THE EMERGENCE OF JADIDISM AND ITS WORK TOWARDS THE DEVELOPMENT OF THE MOTHERLAND (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article will talk about jadidism, its founder, the emergence of jadidism, the main ideas and goals of jadidism, the progressive forces of the time, especially the intelligentsia, realizing the need to reform society, sensing that the local population is lagging behind the world, and the politics of jadidism pursued for the prosperity of the country.